The Response of Cupriavidus metallidurans CH34 to Cadmium Involves Inhibition of the Initiation of Biofilm Formation, Decrease in Intracellular c-di-GMP Levels, and a Novel Metal Regulated Phosphodiesterase - Alviz-Gazitua, Pablo; Fuentes-Alburquenque, Sebastián; Rojas, Luis A.; Turner, Raymond J.; Guiliani, Nicolas; Seeger, Michael (Frontiers in Microbiology, 2019)
Cadmium is a highly toxic heavy metal for biological systems. Cupriavidus metallidurans CH34 is a model strain to study heavy metal resistance and bioremediation as it is able to deal with high heavy metal concentrations. Biofilm formation by bacteria is mediated by the second messenger bis-(3′-5′)-cyclic dimeric guanosine monophosphate (c-di-GMP). The aim of this study was to characterize the response of C. metallidurans CH34 planktonic and biofilm cells to cadmium including their c-di-GMP regulatory pathway. Inhibition of the initiation of biofilm formation and EPS production by C. metallidurans CH34 correlates with increased concentration of cadmium. Planktonic and biofilm cells showed similar tolerance to cadmium. During exposure to cadmium an acute decrease of c-di-GMP levels in planktonic and biofilm cells was observed. Transcription analysis by RT-qPCR showed that cadmium exposure to planktonic and biofilm cells induced the expression of the urf2 gene and the mercuric reductase encoding merA gene, which belong to the Tn501/Tn21 mer operon. After exposure to cadmium, the cadA gene involved in cadmium resistance was equally upregulated in both lifestyles. Bioinformatic analysis and complementation assays indicated that the protein encoded by the urf2 gene is a functional phosphodiesterase involved in the c-di-GMP metabolism. We propose to rename the urf2 gene as mrp gene for metal regulated phosphodiesterase. An increase of the second messenger c-di-GMP content by the heterologous expression of the constitutively active diguanylate cyclase PleD correlated with an increase in biofilm formation and cadmium susceptibility. These results indicate that the response to cadmium in C. metallidurans CH34 inhibits the initiation of biofilm lifestyle and involves a decrease in c-di-GMP levels and a novel metal regulated phosphodiesterase.